Tracing narrative development in children with speech, language, and communication difficulties: a CiteSpace analysis - Ruijie Zhao; Yusong Gao; Yu Cui; Xiaochen Wang (Frontiers in Psychology, 2026)
Narrative development is central to children’s language, communication, and academic functioning, yet children with speech, language, and communication difficulties often experience challenges in organizing and expressing coherent stories. This study used CiteSpace to analyze 628 articles and reviews retrieved from the Web of Science Core Collection and published between 1985 and 2024. The publication trend was descriptively divided into three periods: the Emerging Stage, the Development Stage, and the Growth Stage. Collaboration analyses identified countries, institutions, and authors with relatively high publication output and observable collaborative links. CiteSpace generated seven keyword clusters, which were subsequently synthesized by the authors into four broader themes: Language and Communication Disorders, Cognitive and Social Dimensions of Communication, Medical and Developmental Perspectives, and Speech Rate and Communication Fluency. Keyword co-occurrence analysis identified major research hotspots, while citation burst analysis showed that prevalence and developmental language disorder were prominent recent topics. Overall, the study maps the development, thematic structure, collaboration patterns, and recent areas of scholarly attention in this field and provides directions for future bibliometric and empirical research.